Factors Influencing English Teachers’ Literacy in Assessment for Learning - Sukarno; Nur Hidayanto Pancoro Setyo Putro; Ihtiara Fitrianingsih; Satrio Aji Pramono; Nita Maghfiratul Jannah; Yasir A. Alsamiri; Fadhl Mohammed Awadh Gharamah (Teacher Training and Education Faculty, Widya Gama Mahakam Samarinda University, 2026)
Background:This research explores the factors influencing Assessment for Learning (AfL) literacy among senior high school English teachers in Yogyakarta, Indonesia, drawing on Alonzo's (2016) comprehensive six-dimensional framework. Examining AfL from a sociocultural viewpoint reveals the multifaceted roles of instructors as assessors, pedagogists, student partners, motivators, learners, and stakeholders (Gipps, 1999; Lave & Wenger, 1991). The expertise of teachers in assessment for learning significantly influences the quality of feedback, reflection, and educational outcomes, making assessment literacy essential for effective teaching.Methodology:This quantitative study employed a validated AfL literacy survey, derived from Alonzo (2016), and was administered to 250 English instructors within the Senior High School English Teacher Working Group in Yogyakarta. We employed Confirmatory Factor Analysis (CFA) and Multivariate Analysis of Variance (MANOVA) to investigate the dimensions of AfL literacy and to examine the influence of gender, education, experience, and institutional support on it.Findings:The results showed that educational attainment, teaching experience, and institutional support had a considerable impact on teachers' AfL literacy, while gender did not have a significant effect. Educators with Master’s degrees and over ten years of teaching experience demonstrated enhanced literacy in assessment for learning, particularly in the roles of assessors, pedagogists, and partners with students. Support from the institution enhanced teachers' confidence and sustained their engagement in assessment for learning practices.Conclusion:Transforming conceptual understanding into effective classroom practice requires continuous professional development, support from the school, and regular reflection on practices.Originality:This investigation extends Alonzo’s (2016) framework to the context of Indonesian EFL, systematically identifying demographic and institutional elements that affect AfL literacy, an area that has been rarely examined in educational research within Southeast Asia.